Are All Conservation Measures for Endangered Species Legitimate? Lines of Thinking With the European Hamster - Kletty, Florian; Pelé, Marie; Capber, Fabrice; Habold, Caroline (Frontiers in Ecology and Evolution, 2020)
When dealing with the protection of an endangered species, it appears more and more important to address the ethical limits and the societal perception of the implemented conservation measures. This will be illustrated here through the example of conservation programs of the European hamster (Cricetus cricetus) in France. The main threats for this rodent are the impoverishment and fragmentation of its habitat due to recent changes in agricultural practices and urbanisation. Thus, the status of this species changed from harmful to endangered in only a few decades. This must lead to acceptance of the species by citizens and especially farmers paid to destroy this species until the 1990s while nowadays to protect it. To stem the decline, several measures have been taken through the last twenty years including population reinforcement, wild animal tracking, and implementation of suitable habitats. One can, therefore, discuss the efficiency of these measures and their integration in the entire socio-ecosystem. Population reinforcement and the questions that can arise from it will first be addressed. Secondly, in situ animal monitoring and implications of the methods used will be discussed. Third, we will deal with agricultural practices favourable to the species. Finally, we will highlight the links between European hamster conservation measures and wider problematics.